2011
DOI: 10.1002/dmrr.1237
|View full text |Cite
|
Sign up to set email alerts
|

Pathological changes in the pancreas of fulminant type 1 diabetes and slowly progressive insulin‐dependent diabetes mellitus (SPIDDM): innate immunity in fulminant type 1 diabetes and SPIDDM

Abstract: These findings demonstrate that retinoic acid-inducible protein I (RIG-I)-like helicases and TLRs play a crucial role on beta-cell destruction in enterovirus-induced FT1D. The presence of distinct mechanism(s) of slowly progressive beta-cell failure in SPIDDM was suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Studies of gene-deficient mice indicate that RLRs play an important role in antiviral response [22][23][24]. We have demonstrated significant hyper-expression of RLRs in islet cells of patients with fulminant type 1 diabetes [8,9]. MDA5 was strongly expressed in islet cells (including β-and α-cells) of fulminant type 1 diabetic pancreata.…”
Section: Enterovirus In the Pancreasmentioning
confidence: 81%
See 4 more Smart Citations
“…Studies of gene-deficient mice indicate that RLRs play an important role in antiviral response [22][23][24]. We have demonstrated significant hyper-expression of RLRs in islet cells of patients with fulminant type 1 diabetes [8,9]. MDA5 was strongly expressed in islet cells (including β-and α-cells) of fulminant type 1 diabetic pancreata.…”
Section: Enterovirus In the Pancreasmentioning
confidence: 81%
“…The human TLR multigene family comprises 10 members, with TLR2, -3, -4, -7, and -8 considered to be of importance in the recognition of structural components of RNA viruses, including viral doublestranded RNA, single-stranded RNA, and surface glycoproteins [30]. We showed that both TLR3 and TLR4 were expressed in MNCs that had infiltrated islets of fulminant type 1 diabetic pancreata, but not SPIDDM patients or non-diabetic controls [8,9]. The frequencies of islets with infiltrating MNCs expressing TLR3 and TLR4 were 11.7% and 4.3%, respectively, although almost no islet with MNCs expressing TLR3 or TLR4 was recognized in pancreata of non-diabetic controls or SPIDDM patients.…”
Section: Enterovirus In the Pancreasmentioning
confidence: 82%
See 3 more Smart Citations